Beyond the feathers : examining the mental health of oiled wildlife responders deployed to the MV Rena oil spill, Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Bioscience at Massey University, Manawatū, New Zealand - White, Bridget Jane (Massey University, 2023)
On the 5th October 2011 in Aotearoa New Zealand, the Marine Vessel Rena struck Astrolabe Reef, 12 nautical miles from Tauranga and later was declared New Zealand’s worst maritime environmental disaster. This incident severely impacted wildlife in the region, with 428 live seabirds admitted to the Te Maunga Oiled Wildlife Facility (TMOWF) for treatment and 2063 dead birds collected. The clean-up of oil in the environment and the oiled wildlife response continued for months. An independent review deemed the response to oiled wildlife adequate; however, the emotional toll on wildlife responders was less understood, particularly the impact of stressors on their mental health or attributes of resilience. To understand the mental health impact on oiled wildlife responders attending the Rena oil spill, a qualitative research approach was employed, and in-depth semi-structured interviews were conducted. This approach gained insight into eight wildlife responders’ lived experiences of deployment to the TMOWF. Results indicate that participants placed a high value on contributing their skills and knowledge to assist impacted wildlife. While participants accepted and conducted euthanasia, they expressed more intensity of emotion when confronted by mass mortality from animal death in the field or accidental death in the facility. This appeared to be more challenging to accept than euthanasia and gave rise to feelings of being underprepared. Participants reported using informal coping strategies but lacked training in managing trauma, often relying on past experiences to cope. They reported limited opportunities to formally debrief but instead depended on social connectedness and teamwork to support each other. Recommendations from this research suggest urgent attention to be placed on training primary preventions, integrated into oil spill response planning and operational policy to support mental health, stress management, resilience development and coping strategies of oil spill responders working with wildlife.
Keywords: 520304 Health psychology